Pemberdayaan Masyarakat Dalam Budidaya Teripang (Holothuria scabra) - Santi Penina Tua Rahantoknam; Mariana Yermina Beruatyaan; Mesyke Angel Rahantoknam; Maria Kristina Ohoiwutun (Jurnal Aplikasi dan Inovasi Iptek, 2021)
Watuar Village has mangrove, seagrass and coral reef ecosystems which are also natural habitats for sea cucumbers. Sea cucumbers have been used by the Watuar community by directly catching sea cucumbers to be processed and sold. This habit of taking sea cucumbers causes a decrease in the number of sea cucumbers because the time of taking sea cucumbers has not paid attention to the time or season of sea cucumbers spawning. The purpose of this community service activity is to provide assistance to the community (partners) of Watuar village in sea cucumber cultivation and evaluate the level of partner empowerment in sea cucumber cultivation. Assistance in the cultivation of sea cucumbers was carried out in Watuar village, namely socializing the benefits of mangroves and seagrasses, socializing the gonadal maturity level calendar (TKG) of sea cucumbers, training and implementing the TKG calendar for sea cucumbers, selecting cultivation sites, construction of cultivation containers, making sea cucumber feed, feeding sea cucumbers, measuring growth. sea ​​cucumbers and water quality control. After the implementation of the next activity, an analysis of partner empowerment was carried out using a Likert scale. The results showed a significant increase in partner knowledge and skills by 80% after mentoring in sea cucumber cultivation. From the assistance provided, it can be concluded that the partners are capable and skilled in cultivating sea cucumbers.